Differentiation and magmatic activity in Vesta evidenced by 26Al-26Mg dating in eucrites and diogenites. (1st December 2017) - Hublet, G.; Debaille, V.; Wimpenny, J.; Yin, Q-Z.
Abstract: The 26 Al- 26 Mg short-lived chronometer has been widely used for dating ancient objects in studying the early Solar System. Here, we use this chronometer to investigate and refine the geological history of the asteroid 4-Vesta. Ten meteorites widely believed to come from Vesta (4 basaltic eucrites, 3 cumulate eucrites and 3 diogenites) and the unique achondrite Asuka 881394 were selected for this study. All samples were analyzed for their δ 26 Mg∗ and 27 Al/ 24 Mg ratios, in order to construct both whole rock and model whole rock isochrons. Mineral separation was performed on 8 of the HED's in order to obtain internal isochrons. While whole rock Al-Mg analyses of HED's plot on a regression that could be interpreted as a vestan planetary isochron, internal mineral isochrons indicate a more complex history. Crystallization ages obtained from internal 26 Al- 26 Mg systematic in basaltic eucrites show that Vesta's upper crust was formed during a short period of magmatic activity at 2.66 - 0.58 + 1.39 million years (Ma) after Calcium-Aluminum inclusions (after CAI). We also suggest that impact metamorphism and subsequent age resetting could have taken place at the surface of Vesta while 26 Al was still extant. Cumulate eucrites crystallized progressively from 5.48 - 0.60 + 1.56 to >7.25 Ma after CAI. Model ages obtained for both basaltic and cumulate eucrites are similar and suggest that the timing of differentiation of a common eucrite source from a chondritic body can be modeled at 2.88 - 0.12 + 0.14 Ma after CAI, i.e. contemporaneously from the onset of the basaltic eucritic crust. Based on their cumulate texture, we suggest cumulate eucrites were likely formed deeper in the crust of Vesta. Diogenites have a more complicated history and their 26 Al- 26 Mg systematics show that they likely formed after the complete decay of 26 Al and thus are younger than eucrites. This refined chronology for eucrites and diogenites is consistent with a short magma ocean stage on 4-Vesta from which the basaltic eucrites rapidly crystallized. In order to explain the younger age and the complex history of diogenites, we postulate that a second episode of magmatism was possibly triggered by a mantle overturn. We bring a refined chronology of the geological history of Vesta that shows that the asteroid has known a more-complex differentiation than previously thought.